Fidel Valdez Ramos [Philippines, President] - Ramos, Fidel Valdez (Institutional Knowledge at Singapore Management University, 2015)
Fidel V Ramos was the 12th President of the Philippines. As Director-General of the Integrated National Police and Acting Chief of Staff of the Armed Forces of the Philippines, he rose up against the dictatorship of President Ferdinand Marcos, to lead the military in the People Power Revolution of 1986. He tells DNA why he decided to stand up to his second cousin, what led him to run for the presidency and the thinking behind one of the key achievements of his term - the peace agreement with the MNLF.